2014
DOI: 10.3389/fgene.2014.00091
|View full text |Cite
|
Sign up to set email alerts
|

Expression of microRNAs in bovine and human pre-implantation embryo culture media

Abstract: MicroRNAs (miRNA) are short non-coding RNAs which act to regulate expression of genes driving numerous cellular processes. These RNAs are secreted within exosomes from cells into the extracellular environment where they may act as signaling molecules. In addition, they are relatively stable and are specifically expressed in association to certain cancers making them strong candidates as biological markers. Moreover, miRNAs have been detected in body fluids including urine, milk, saliva, semen, and blood plasma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
130
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(136 citation statements)
references
References 44 publications
4
130
0
2
Order By: Relevance
“…MSC-derived exosomal microvesicles have been recently documented and may provide a potential explanation for the micromodulation potential observed with stem cells. Moreover, it was recently shown that human and cattle preimplantation embryos also secreted exosomes throughout the in vitro culture period [31,32]. Therefore, one may also speculate a potential reciprocal effect between b-ATMSCs and embryos in culture that may explain the observed effects.…”
Section: Discussionmentioning
confidence: 96%
“…MSC-derived exosomal microvesicles have been recently documented and may provide a potential explanation for the micromodulation potential observed with stem cells. Moreover, it was recently shown that human and cattle preimplantation embryos also secreted exosomes throughout the in vitro culture period [31,32]. Therefore, one may also speculate a potential reciprocal effect between b-ATMSCs and embryos in culture that may explain the observed effects.…”
Section: Discussionmentioning
confidence: 96%
“…The same year, placental miRNAs were found circulating in maternal plasma , which was one of the discoveries leading to the notion that miRNAs could be a mobile regulating molecule (Iguchi et al, 2010) and that could even mediate transgenerational epigenetic heritance (Sharma, 2015) or be transmitted across species Buck et al, 2014). Since then, extracellular miRNAs were identified in a broad range of biological fluids, including plasma, aqueous humour, cerebrospinal fluid, nasal mucus, or milk (Pegtel et al, 2011;Huang et al, 2013b;Kropp et al, 2014;Baglio et al, 2015;Dismuke et al, 2015;Wu et al, 2015a). miRNAs were identified in the cargo of exosomes, membranous vesicles 40 to 100 nm in diameter, which are constitutively released by almost all cell type and are found essentially in every biological fluid (reviewed, for example, in (Rak, 2013;Yoon et al, 2014) However, extracellular miRNAs do not need to be necessarily encapsulated in extracellular vesicles, as two studies showed that 95-99% of extracellular miRNA are not in extracellular vesicles but associated with AGO proteins in serum and cell culture media (Arroyo et al, 2011;Turchinovich et al, 2011).…”
Section: Extracellular Micrornasmentioning
confidence: 99%
“…Aberrant miRNA profiles in transferable blastocysts have been linked with male factor infertility and polycystic ovaries [5]. Since miRNAs are known to be secreted [18], attempts have been made to link specific miRNAs detected in the SBM with embryo ploidy status and reproductive competence [2][3][4][5]. miRNAs detected in the spent medium from early embryos might be the output of paracrine circuits, reflecting normal communication among cells of healthy embryos; alternatively, they might be a component of the communication pathway between the embryo and the uterine epithelium, influencing epithelial readiness for embryo apposition and implantation.…”
Section: Microrna Profile In Sbms Is Similar Among Twins a And B Butmentioning
confidence: 99%
“…For example, miR-30b is involved in development of embryonic ectoderm [22], miR-373 promotes mesendoderm differentiation [23], and miR-24 is required for hematopoietic differentiation [24]. However, only miR-24 [25,26] and miR-25 [3] were detected in preimplantation embryo culture media.…”
Section: Microrna Profile In Sbms Is Similar Among Twins a And B Butmentioning
confidence: 99%
See 1 more Smart Citation